GROWTH RATE IN LACTARIUS LACTARIUS (SCHNEIDER) AT KARWAR - Kartha, K N Rasachandra (Indian Journal of Fisheries, 2011)
The length-frequency data of the big-jawed jumper, Lactarius lactarius(Schneider), collected from the trawl catches of Karwar coast during 1965-66,1966-67 and 1967-68 season show that the species attains a length of about 90 mmin six months. The landings from grounds more than 30 meters in depth generallycontained bigger individuals, while the near-shore catches were dominated byjuveniles.